2014
DOI: 10.5505/1304.7361.2014.48802
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Overcrowding in the Emergency Department: Experiences and Suggestions of an Education and Research Hospital

Abstract: SUMMARYObjectivesIn this study, we aimed to determine the causes of overcrowding in the Emergency Department (ED) and make recommendations to help reduce length of stay (LOS) of patients in the ED.MethodsWe analyzed the medical data of patients admitted to our ER in a one-year period. Demographic characteristics, LOS, revisit frequency, and consultation status of the patients were determined.ResultsA total of 163,951 patients were admitted to our ED between January 1, 2013, and December 31, 2013. In this perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 14 publications
1
57
0
7
Order By: Relevance
“…Increasing the number of consultant visits to the ED leads to the increasing ED LOS and the ED crowding (2,16,20,22). The most time consume process in consultation is the time arriving of consultant to the ED.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the number of consultant visits to the ED leads to the increasing ED LOS and the ED crowding (2,16,20,22). The most time consume process in consultation is the time arriving of consultant to the ED.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, it was reported that the patients' average LOS in the emergency department was 183.6 minutes (~three hours) [10]. In another study, avarage LOS in the ED was reported to be 164.1 minutes [2]. For the 900 patients included in the study by Mahmoodian et al revealed that the median waiting time from arrival to first visit by physician was 8 (5 -14) minutes [13].…”
Section: Discussionmentioning
confidence: 97%
“…Overcrowding is one of the most important problems in the ED which causes decrease in EM popularity. It causes not only motivation disorders of employee but also degradation of the quality of care, increased costs and patients' dissatisfaction [2] [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations